The study of antimicrobial activity of 2-((4-R-3-(morpholinomethylene)-4H-1,2,4-triazole-5-yl)thio)acetic acid salts - R. О. Shcherbyna; O. I. Panasenko; Ye. G. Knysh; H. A. Fotina; E. V. Vashchyk; T. I. Fotina (Zaporožskij Medicinskij Žurnal)
The purpose of the work was to study the antimicrobial activity of 2-((4-R-3-(morfolinomethylene)-4H-1,2,4-triazole-5-yl)thio) acetic acid salts by "hanging drop" and “serial dilution” methods in broth (limiting concentration option) and establish some patterns of "structure – action" depending.